E-government and simplification of administrative processes in the Provincial Municipality of Huanuco in the context of COVID-19 - Calero, Roberto (2023)
Objective. To determine the relationship between the implementation of e-government and the simplification of administrative processes in the Provincial Municipality of Huanuco (MPHCO), Huanuco region (Peru), in the context of COVID-19. Methods. The research was characterized as basic, with a descriptive-correlational level and a non-experimental design. The public management approach based on the modernization and digitalization of the State was used. Data collection was carried out through the application of a survey questionnaire to 372 citizen users of municipal services, from 2020 to the present, and with this, the correlation between variables was estimated. Results. Evidence was found of a positive association between the implementation of e-government and the simplification of municipal administrative processes. In particular, the value of the correlation coefficient between the implementation of e-government and the simplification of requirements, costs and deadlines was found to be 0.486, 0.351 and 0.472, respectively. Conclusions. It can be affirmed that the implementation of ICT in MPHCO management since the COVID-19 pandemic has contributed to making administrative processes simpler for citizens who demand municipal products/services.